Gamma Radiation-Induced Damage in the Zinc Finger of the Transcription Factor IIIA - XiaoHong Zhang; YuJi Miao; XiaoDan Hu; Rui Min; PeiDang Liu; HaiQian Zhang (Bioinorganic Chemistry and Applications)
A zinc finger motif is an element of proteins that can specifically recognize and bind to DNA. Because they contain multiple cysteine residues, zinc finger motifs possess redox properties. Ionizing radiation generates a variety of free radicals in organisms. Zinc finger motifs, therefore, may be a target of ionizing radiation. The effect of gamma radiation on the zinc finger motifs in transcription factor IIIA (TFIIIA), a zinc finger protein, was investigated. TFIIIA was exposed to different gamma doses from 60Co sources. The dose rates were 0.20 Gy/min and 800 Gy/h, respectively. The binding capacity of zinc finger motifs in TFIIIA was determined using an electrophoretic mobility shift assay. We found that 1000 Gy of gamma radiation impaired the function of the zinc finger motifs in TFIIIA. The sites of radiation-induced damage in the zinc finger were the thiol groups of cysteine residues and zinc (II) ions. The thiol groups were oxidized to form disulfide bonds and the zinc (II) ions were indicated to be reduced to zinc atoms. These results indicate that the zinc finger motif is a target domain for gamma radiation, which may decrease 5S rRNA expression via impairment of the zinc finger motifs in TFIIIA.